Chronic diseases of Hahnemann in the light of microecology - Linder, Reinhold (British Homeopathic Journal, 1989)
The management of Hahnemann's ‘chronic diseases’ presents certain difficulties. In particular the difficulty of finding a suitable homœopathic drug is noted.Bach's and Paterson's work on bowel nosodes opened a totally new way of looking at homœopathy and chronic disease (miasms). Since their time the homœopathic profession has done little to take their research further.Parallel to the work of Bach and Paterson continental bacteriologists and clinicians developed therapeutic concepts based on intestinal microbes. Their research has become internationally respected and is part of the new sciences of microecology (microbes vs. host association) and gnotobiology (germfree research on animals). Both these sciences allow for additional diagnostic and therapeutic insights that are relevant to homœopathy.Although the non-lactose fermenters, as defined by Bach and Paterson, are important in chronic disease, other bacteria have equal significance. The ecology of microbe and host, as expressed in their qualitative relatedness, needs to be better understood.The author's effort over many years has been to correlate and integrate these modern findings of bowel flora research and autogenous vaccines with his homœopathic practice. It is suggested that, apart from the therapeutic benefits to be gained by this approach, modern faecal bacteriology analysis could become a useful monitoring tool to evaluate the response to medicines prescribed on homœopathic principles.
Keywords: Chronic disease; Bowel nosodes; Vaccine therapy; Microecology; Gnotobiology; Symbiosis